Integrating Authentic Assessment and Reflective Learning to Enhance Learner Autonomy in Secondary Education - Muhammad Saopi; Dedi Wahyudi; Ahmad Maulana (Gema Cendekia Institute, 2025)
Learner autonomy has become a central goal in contemporary secondary education as schools seek to prepare students for lifelong learning and active participation in complex academic and social environments. However, the development of learner autonomy remains constrained by traditional assessment practices that emphasize summative outcomes and teacher-directed learning. This study investigates the effectiveness of integrating authentic assessment and reflective learning in enhancing learner autonomy among secondary school students. Employing a mixed-methods, quasi-experimental design, the study was conducted in a secondary education context over one academic term. Quantitative data were collected through a learner autonomy questionnaire administered before and after the instructional intervention, while qualitative data were obtained from students’ reflective journals, open-ended survey responses, and classroom observations. The instructional intervention involved the systematic use of authentic assessment tasks, such as project-based and performance-oriented activities, combined with structured reflective learning practices, including self-assessment, peer feedback, and guided reflective journals. The findings indicate a significant improvement in students’ learner autonomy, particularly in the areas of self-monitoring, decision-making, and learning responsibility. Qualitative analyses further reveal that reflective learning played a crucial role in deepening students’ awareness of learning processes and fostering a sense of ownership over assessment tasks. Students reported increased engagement and perceived learning as more meaningful and relevant when assessment was connected to real-world contexts. Overall, the study demonstrates that the integration of authentic assessment and reflective learning provides a viable pedagogical approach for promoting learner autonomy in secondary education. The findings offer practical implications for teachers and educational policymakers seeking to implement autonomy-supportive assessment practices.